The Association between iron deficiency anaemia and academic performance of children focusing on grade II pupils in the Winterveldt region, Tshwane North, South Africa - Hlatshwayo, Bongiwe P. S. (University of Limpopo (Medunsa Campus), 2011)
ABSTRACT BACKGROUND AND OBJECTIVES: Iron deficiency anaemia (IDA) is the most common nutritional disorder in the developing world. A large number of children under the age of 5 years do not reach their developmental potential, IDA and iron deficiency being well documented risk factors. IDA has been shown to be an important cause for decreased attention span, reduced alertness and learning difficulties in both young children and adolescents. South Africa has a growing burden of anaemia and iron deficiency and the most affected areas are the poor communities. There is vast evidence on the negative effects of iron deficiency to a child's developing brain from studies done internationally but limited data on the subject in South Africa, despite the huge burden of iron deficiency. We investigated the association between IDA and school performance and intelligence and also determined the local prevalence of IDA in the Winterveldt region, North of Tshwane, South Africa. METHODS: Three primary schools from Winterveldt were sampled. All subjects with parental consent were screened for anaemia using Hemocue 201+ Hb meter (n=194). Blood for iron studies and CRP was collected on all anaemic pupils (n=75) to define IDA (Hb<I1.5g/dl, ferritin<12ug/L and CRP<10). Cases and controls were recruited after results using matching anthropometry at a 1:2 ratio (one case to two controls). A total of 90 pupils (30 cases & 60 controls) were compared using 2009 school reports. Analysis was done per subject using the national scoring system, where one means incompetent and four means excellent achievement. The Raven's Coloured Progressive Matrices (RCPM) was used as our psychometric test and scores were recorded as percentiles and interpreted by the educational psychologist who conducted the test. RESUL TS: Point prevalence of iron deficiency anaemia for the Winterveldt region was found to be 9.8%. The prevalence of under-weight was 19% and that of stunting 23% with no significant differences between cases and controls (P=0.368 for under-weight and p=0.863 for stunting). There was no statistically significant association between IDA and performance in mathematics (X2=1.34 and p=0.511). However, cases scored poorly in life skills (P=0.00017) and in literacy the test for level of significance approaches significance (P=0.071). There was also no statistically significant association between IDA and low scores on the RCPM test (X2=3.31 and p=0.65). CONCLUSION: The point prevalence was high compared to the national prevalence of IDA which is about 5%. This could be related to a number of factors including the socio-economic background of the pupils. Since dietary history and knowledge of fortified food was not investigated, we cannot draw conclusions on the cause of this high prevalence. The study also found that the general population was under-nourished, which is consistent with the poor socio¬ economic status of the study area. However, our participants were more under-weight and stunted when the data was compared with previous national surveys. The study found a negative correlation between IDA and two areas of academic performance which is consistent with international data. In mathematics however, we believe that the low curriculum standard in all South African schools affected the outcome. The results of the psychometric test were not consistent with international data where most studies showed a negative correlation between IDA and the Ravens Matrices. South African studies have demonstrated poor performance of black students on the Ravens Matrices when compared to other races and our results followed this trend as our scores were similar to most of the studies.
Thesis (M Med (Paediatrics and Child Health)) -- University of Limpopo, 2011.
Keywords: Iron; Anaemia